(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the anthropometric indices in newborns at Hue University of Medicine and Pharmacy Hospital. Subjects and methods: A cross-sectional descriptive study was conducted on 1170 newborns delivered at the Obstetrics and Gynecology Department, Hue University of Medicine and Pharmacy Hospital from January 2023 to July 2024. Results: A total of 1170 newborns were included in the study. Gestational ages ranged from 26 to 42 weeks, with a mean gestational age of 38.2 ± 2.2 weeks, the mean birth weight was 3000.57 ± 586.7 grams. Male newborns had higher mean values for weight, length, head circumference, arm circumference, and foot length compared to female newborns. For full-term newborns at 40 weeks of gestation, mean birth weight was 3274.52 ± 370.6 grams, mean length was 49.90 ± 2.3 cm, mean head circumference was 33.82 ± 1.38 cm, mean arm circumference was 10.12 ± 1.02 cm, and mean foot length was 7.93 ± 0.51 cm. Conclusions: In this study, the anthropometric indices of newborns with the same gestational age were found to be when lower compared to the growth charts of Fenton 2013 or Intergrowth-21st. This suggests a need for developing a growth chart for Vietnamese newborns to assess nutritional status appropriately.